Large-scale Wind Power Integration in Northern Norway - Singh, Arwinder (UiT Norges arktiske universitet, 2018)
Norway has very high flexibility in energy production since hydropower covers about 95% of yearly energy demand. It is best to have a combination of wind and hydropower and hence it applies perfectly here in Norway. The performance of the wind farm can be significantly enhanced by employing full-capacity converters. The state-of-the-art literature study has been done on Squirrel Cage Induction Generator connected to the grid via two-level voltage source converter. The thesis is further focused on modeling a wind farm as a single machine equivalent to provide 100 MW to the grid by having a best possible way to integrate it into the regional grid of Northern Norway. The primary attention was given to Power converter and Squirrel Cage Induction Generator as they are main electrical components. Mathematical models of induction generator and power converter are studied in depth emphasizes on optimal ways of controlling mechanism. Analysis of grid connection methods is focused primarily based on Northern Norway grid’s voltage rating. Steady-state analysis of the system is properly performed. Five case studies are presented which were performed in DIgSILENT © PowerFactory software, and results are examined and discussed. Finally, the discussion and conclusion have been presented.